2018
DOI: 10.1108/reps-10-2018-015
|View full text |Cite
|
Sign up to set email alerts
|

What empowers Egyptian women: resources versus social constrains?

Abstract: Purpose This paper aims to tackle an important question related to women’s economic empowerment in highly patriarchal societies like Egypt. The paper discusses individual, household, wealth and location factors determining women empowerment, as measured by two dimensions: decision-making power and mobility. Design/methodology/approach Using the “Egypt Labor Market Panel Survey” (ELMPS) 2012, a Multiple Indicators Multiple Causes (MIMIC) model was estimated to study the main economic resources and social cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
2
10
1
Order By: Relevance
“…Mainuddin et al (2015), in a study on Bangladesh, found that women's empowerment correlated with their husbands' education levels. That result differs from (Nazier & Ramadan, 2018), in his study on Egyptian women, in that all education categories, as compared to the illiterate category, did not have a significant effect on empowerment in its two dimensions, decisions and mobility. He described that result as surprising and referred it to the education system in Egypt, which could not change the intellectual system of its community members to achieve gender equality.…”
Section: Empowerment and Educationcontrasting
confidence: 65%
See 1 more Smart Citation
“…Mainuddin et al (2015), in a study on Bangladesh, found that women's empowerment correlated with their husbands' education levels. That result differs from (Nazier & Ramadan, 2018), in his study on Egyptian women, in that all education categories, as compared to the illiterate category, did not have a significant effect on empowerment in its two dimensions, decisions and mobility. He described that result as surprising and referred it to the education system in Egypt, which could not change the intellectual system of its community members to achieve gender equality.…”
Section: Empowerment and Educationcontrasting
confidence: 65%
“…As for the effect of education on empowerment, studies have shown that women's empowerment is significantly related to the husbands' education levels (Alishah et al, 2019;Mainuddin, Begum, Rawal, Islam, & Islam, 2015;Samari, 2019), whereas (Alishah et al, 2019;Nazier & Ramadan, 2018) did not show a significant correlation between women's empowerment and their education levels, but it showed significance in (Samari, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While there are many factors that can shape women's agency, studies demonstrate that individual characteristics like age, marital status, women's age at marriage, education, and employment are important determinants of agency. [38][39][40][41][42] Education and employment give women a greater sense of personal control. In Egypt, later age at marriage provides more opportunity for education, employment, and participation in the choice of a husband, which can enhance women's negotiating power within the households.…”
Section: Measures Of Agencymentioning
confidence: 99%
“…Previous research has shown that different types of work are differentially accessible to women in MENA countries depending on their education and stage in life (Nazier and Ramadan 2018;Hendy 2015bHendy , 2011Hendy , 2020Assaad andEl-Hamidi 2001, 2009;Assaad, Hendy, and Yassine 2014). Specifically, less educated women tend to have limited access to wage work and are often confined to home-based selfemployment or unpaid family work, if they participate in the labor force at all.…”
Section: Introductionmentioning
confidence: 99%